2020
DOI: 10.3390/ph13080193
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal and In Vitro Cytotoxicity of Moringa oleifera Seed Extract and Its Elemental Analysis Using Laser-Induced Breakdown Spectroscopy

Abstract: In the current study, we present the correlation between the capability of laser-induced breakdown spectroscopy (LIBS) to monitor the elemental compositions of plants and their biological effects. The selected plant, Moringa oleifera, is known to harbor various minerals and vitamins useful for human health and is a potential source for pharmaceutical interventions. From this standpoint, we assessed the antibacterial and in vitro cytotoxicity of the bioactive components present in Moringa oleifera seed (MOS) ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 35 publications
1
22
0
1
Order By: Relevance
“…This is the first study demonstrating the cell viability of MSNPs against HCT-116 and HeLa cells. We have previously reported the impact of different nanomaterials on colon and breast cancer cells [ 36 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first study demonstrating the cell viability of MSNPs against HCT-116 and HeLa cells. We have previously reported the impact of different nanomaterials on colon and breast cancer cells [ 36 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…As per previously described method [34,35], the cells were cultured and maintained in the DMEM media, L-glutamine (5%), penicillin (1%), streptomycin (1%), FBS (10%) and selenium chloride (1%) in (5%) a CO 2 incubator (Thermo-Fisher Scientific, Inc., Waltham, MA, USA) at 37 • C. The cells were seeded in 96 well culture plates and they reached 75-80% confluence. They were processed for testing samples using MTT assay (Baig et al, 2020;Rehman et al, 2020). The MTT assay was done as per the previous study and the (HCT-116, HeLa and HEK-293, ATCC, Manassas, VA, USA) cells were treated with MSNPs with dosages ranging from 5.0 µg to 75 µg/mL.…”
Section: Anti-cancer Activity 221 Cell Culture and Testing Of Msnpsmentioning
confidence: 99%
“…We previously reported the impact of different nanomaterials on colon and breast cancer cells [ 45 , 46 , 47 ]. The presence of cobalt complexes in the nanocomposites may change the count and length of aliphatic chains, within the coordinated ligands.…”
Section: Resultsmentioning
confidence: 99%
“…This is the first study that demonstrates the inhibitory effect on cell viability of synthesized Co 0.5 Ni 0.5 Ga x Fe 2−x O 4 (0.0 ≤ x ≤ 1.0) MCs against HCT-116 and HeLa cells. We previously reported the impact of different nanomaterials on colon and breast cancer cells [45][46][47]. The presence of cobalt complexes in the nanocomposites may change the count and length of aliphatic chains, within the coordinated ligands.…”
Section: Microstructural Analysis Of Co0mentioning
confidence: 99%
“…A study by A. Baycal et al [9] on Moringa oleifera reported the correlation between the capability of laser-induced breakdown spectroscopy (LIBS) to monitor the elemental compositions of plants and their biological effects. In particular, the bioactive components of the seed (MOS) alcoholic extract were tested against Escherichia coli and Staphylococcus aureus via an agar well diffusion (AWD) assay and scanning electron microscopy (SEM).…”
mentioning
confidence: 99%